The Monitoring Committee for RTD - Rossano M.; Bonfim J.; Chaabouni R.; Bonas G. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
The history of Barcelona process for Science and Technology coincides somehow with the activities of the MoCo, the Senior Official Forum that was created to monitor and strengthen Euro-Mediterranean cooperation in Research and Innovation. The role and the results achieved so far by the MoCo, which celebrates its 17th year of existence, are discussed with a view to contributing to better face the main future challenges, integrate and coordinate research and innovation actions and find proper solutions to bottlenecks and problems that still hamper the process toward the creation of the Euro-Mediterranean research and innovation area.